The Concept of Child Education Through Dodaidi in Aceh - Idris, Saifullah; Syahril, Syahril (Jurnal Ilmiah Peuradeun, 2019)
Enchanting lullabies for children is one of Aceh's traditions that has been inherited from generation to generation to be preserved. Poetry songs containing moral teaching, values and principles of a child's life will be useful for children in the future. Undeniably, enchanting activities to accompany child sleeping among the people of Aceh is a form of the first social interaction between mother and child. In Aceh, the habits of mothers to put their children to sleep while enchanting Dodaidi, is known as Peulale euh aneuk (stretchers when children sleep). This study aims to retrace whether the traditional process of swing (dodaidi) is still being carried out in Aceh or not. This research is expected to be one of the ways to anticipate the swing tradition from extinction, as well as to preserve and maintain the traditional heritage of Aceh which has been forgotten. The results showed that the process of swinging (dodaidi) was still carried out by housewives in Aceh and was the experience and ability of a mother in transmitting and presenting advice, guidance and messages in the form of poetry when children were lulled. Dodaidi is a process of swing carried out by the mother when the child is about to be put to sleep and is an educational concept in Aceh.